Phosphorus-Modified Palladium and Tungsten Carbide/Mesoporous Carbon Composite for Hydrogen Oxidation Reaction of Proton Exchange Membrane Fuel Cells - Ganghong Bae; Woo Jin Byun; Jin Ho Lee; Min Hee Lee; Yeji Choi; Jae Young Kim; Duck Hyun Youn (Nanomaterials, 2024)
A composite material of tungsten carbide and mesoporous carbon was synthesized by the sol-gel polycondensation of resorcinol and formaldehyde, using cetyltrimethylammonium bromide as a surfactant and Ludox HS-40 as a porogen, and served as a support for Pd-based electrodes. Phosphorus-modified Pd particles were deposited onto the support using an NH3-mediated polyol reduction method facilitated by sodium hypophosphite. Remarkably small Pd nanoparticles with a diameter of ca. 4 nm were formed by the phosphorus modification. Owing to the high dispersion of Pd and its strong interaction with tungsten carbide, the Pd nanoparticles embedded in the tungsten carbide/mesoporous carbon composite exhibited a hydrogen oxidation activity approximately twice as high as that of the commercial Pt/C catalyst under the anode reaction conditions of proton exchange membrane fuel cells.